Mathematical Model of the Thermal Performance of Double-Pass Solar Collector for Solar Energy Application in Sierra Leone - Abu Bakarr Momodu Bangura; Ridho Hantoro; Ahmad Fudholi; Pierre Damien Uwitije (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The primary aim of this study was to utilize thermal energy for drying applications on March 21 (day of the year, n = 80) for the climatic weather conditions of Freetown, Sierra Leone. We evaluated the heat absorption of a double-pass solar air collector based on its configuration and exterior input variables before it was designed and mounted at the location of interest. This study considered a steady-state heat transfer using the thermal network procedure for thermodynamic modeling of a double-pass solar collector developed for drying and heating purposes. A mathematical model defining the thermophysical collector properties and many heat transfer coefficients is formed and numerically solved for this purpose. Indeed, this helped us generate the hourly temperature of different heat collector components, which aided in the performance evaluation of the system. The impact of the fluid flowing inside the collector on the temperature of the exit air was analyzed. It was observed that a flow rate of 0.02 kg/s produced an output of 91.72°C. The system's thermal efficiency improves with increased flow rate at various solar radiation intensities. It was observed that the thermal efficiency of the collector increases from 29% to 67% at flow rates of 0.01–0.3 kg/s. Collector lengths of 1.4 and 2.4 m are observed to be economically viable. An increase in the flow rate caused an increase on the efficiency. The hourly outputs for the collector components were represented graphically, and the curve patterns were similar to those of previous studies.